Manufacturing strategy formation process: case study of iranian manufacturing companies / Gamybos strategijos formavimo procesas Irano gamybos įmonėse - Sepehr Ghazinoory; Rahman Mahdiani Khotbesara; Sedigheh Rezaeian Fardoei (Technological and Economic Development of Economy, 2012)
This paper describes case study research undertaken in six Iranian manufacturing companies aimed at advancing the understanding of the manufacturing strategy formation process. As shown in this study, culture, leadership, policy and incrementalism have their own undeniable roles in manufacturing strategy formation. Cultural factors impact on political factors, and political factors impact on individual factors. It could be useful To utilize formal business planning for firms interested in deliberative manufacturing strategy. In this study, we use Barnes's manufacturing strategy formation process as frameworks with some new changes. Also a case study methodology was used to investigate the process of formation of manufacturing strategy in six small manufacturing companies in Iran like Barnes did in the UK. The results of this study are the main features of the process of manufacturing strategy formation and manufacturing strategy formation model in the case companies. In the case study method, external validity is inevitably compromised due to the limited number of companies that can be studied. The demonstrated model in this study offers a comprehensible view in organizational and external contexts that can be used by manufacturing decision makers.